Comparative analysis of reduce the viscosity of coal-water fuels - G. R. Mingaleeva (Известия высших учебных заведений: Проблемы энергетики, 2017)
The mechanism of action and the effect of plasticizing agents on the rheological properties of the suspensions, the solid phase of which is represented monodisperse and bifractional coal dusts have been studied. The results of experimental studies of the viscosity of coal-water fuel with the content of the Kuznetsk coal brand T 60% (wt.), the fine fraction of which is 5% solids have been given. The dependence of the dynamic viscosity of coal-water fuel shear rate using different plasticizers: soda and baking soda, sodium sulphite and technical lignosulfonate have been obtained. It was found that the most effective of these plasticizers is technical lignosulfonate.